Influence of particle fragmentation and non-sphericity on the determination of diffusive and kinetic fluidized bed biochar combustion data - Pereira, C C; Pinho, C (Fuel, 2014)
In several studies of batch combustion of mineral or vegetal coal in fluidized bed reactors, it is assumed that the fragmentation of the fuel particles is meaningless and also that these particles are spheres. None of these assumptions is corrected although they are commonly accepted in many design and calculation procedures. Here the influence of the above mentioned phenomena on the experimentally obtained diffusive and kinetic data are compared with the equivalent results previously obtained by ignoring such occurrences. Four chars made from typical woods from the Portuguese forest were tested. The results show that for the studied chars, ignoring the phenomenon of fragmentation, diffusive and kinetic data are overestimated by about 5–10%, whereas not taking into account the actual shape of the particles overestimates the diffusive data between 45% and 50% and the kinetic data between 25% and 30%. This highlights the extreme importance of particle shape in the study and modeling of char combustion in fluidized bed reactors.
Keywords: biomass; Combustion; Fluidized bed

Kinetic and diffusive data from batch combustion of wood chars in fluidized bed - Rangel, N; Pinho, C (Biomass and Bioenergy, 2011)
In this work it is studied the combustion of batches of wood char particles in a shallow ﬂuidized bed at laboratory scale. Commercial and recarbonized chars from nut pine and cork oak parent woods were burned for bed temperatures of 600e750 C and particle sizes range of 1.8e3.6 mm. A combustion model based on the two-phase theory of ﬂuidization is presented to evaluate the global combustion resistance. Sherwood numbers and kinetic constants for the heterogeneous phase reaction are also assessed. Through the comparison among theoretical and experimental results, conclusions are drawn on the combustion mechanism as well as on the combustion controlling resistance. The Arrhenius law is proposed to predict the kinetic constants for the studied chars
Keywords: Experimental data; Fluidized bed combustion; Kinetic constant; Modeling; Wood char